Taxonomic assessments of some Cyprinotinae Bronstein, 1947 species (Crustacea: Ostracoda) from Japanese and Korean rice fields, including (re-) descriptions of six species and a review of the type species of the subfamily - Smith, Robin James; Chang, Cheon Young (Zootaxa, 2020)
Rice is the staple food crop for approximately half the world’s population, but some common and abundant taxa inhabiting rice fields, such as ostracods, are poorly studied. For many ostracod species only brief, initial descriptions are available, hindering reliable identifications, and so their ecological roles in rice fields remain obscure. This study partially addresses this problem by assessing the taxonomic validity of six species of Cyprinotinae ostracods reported from rice fields in Japan and South Korea: Cyprinotus uenoi Brehm, 1936, Hemicypris megalops Sars, 1903, Hemicypris ovata Sars, 1903, Hemicypris vulgaris Okubo, 1990, Heterocypris rotundata (Bronstein, 1928), and Hemicypris kawagaensis Okubo, 2004 nomen nudum. Type material of C. uenoi was not designated and Brehm’s ostracod collection is missing, but Japanese and Korean records of C. uenoi differ significantly from Brehm‘s original description. The Japanese and Korean species is described and named herein as Cyprinotus cassidula sp. nov. Japanese specimens reported to be Hemicypris megalops are probably misidentified, but details of the carapace of Hemicypris megalops are obscure due to poor preservation of type material. Examination of topotype material of Hemicypris posterotruncata Bate, 1970, a sub-fossil from near Lake Turkana in Kenya, demonstrates that this species is extant in Asian rice fields. Investigation of type material of Hemicypris kliei (Lindroth, 1953) has revealed that it is not a senior synonym of Hemicypris posterotruncata, contrary to previous studies. Size and morphological data indicates that Hemicypris vulgaris is a large form of Hemicypris posterotruncata and the two species are treated as synonyms herein. Examination of paralectotypes of Hemicypris ovata indicates that it is very similar to Hemicypris posterotruncata, especially the larger morphotypes, but as these two species can be distinguished by morphological features they are both retained as separate species. However, Japanese records of Hemicypris ovata are considered misidentifications of the larger forms of Hemicypris posterotruncata. Hemicypris kawagaensis, which has only been reported once from East Asia, is herein regarded as a junior synonym of Hemicypris barbadensis Broodbakker, 1983, and is likely an alien species in Asia. Asian specimens previously identified as Heterocypris rotundata show sufficient differences to European specimens to determine that they are not conspecific. This species is described as Heterocypris savatenalintonae sp. nov. Taxonomic descriptions of Hemicypris ovata, Hemicypris posterotruncata, Hemicypris megalops, Hemicypris kliei, Heterocypris savatenalintonae sp. nov., and Cyprinotus cassidula sp. nov. are presented. Finally, it is noted that past redescriptions of Cyprinotus cingalensis Brady, 1886, the type species of the genus and the subfamily Cyprinotinae Bronstein 1947, are based partly on other species.